2020
DOI: 10.1177/0011128720902699
|View full text |Cite
|
Sign up to set email alerts
|

Race, Ethnicity, Crime Type, and the Sentencing of Violent Felony Offenders

Abstract: Within the large body of literature on racial/ethnic disparities in criminal sentencing, some research has demonstrated that these relationships are conditional upon various legally relevant case characteristics, including the type of offense for which the defendants are sentenced. To date, however, few studies have explored the potential moderating effects of different violent crimes. Using data from Florida ( N = 186,885), the findings from these analyses indicate that Black–White sentencing disparities are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 74 publications
(162 reference statements)
1
2
0
Order By: Relevance
“…Similar results also have been observed in studies of non-traditional sentencing outcomes, including the assignment of the habitual offender designation (Caravelis et al, 2011;Crawford et al, 1998) and the withholding of felony adjudication (Bontrager et al, 2005). However, within the broad categories of violent and drug offenses, there is mixed evidence that racial/ethnic disparities are amplified in less serious cases (Kautt & Spohn, 2002;Lehmann, 2020;Spohn & Cederblom, 1991;Steen et al, 2005). The interactive effects of minority status and criminal history are likewise somewhat inconsistent; while some work has revealed aggravated disparities among offenders with little or no prior record (e.g., Franklin & Henry, 2020;Hester & Hartman, 2017;Spohn & Cederblom, 1991), others have found the opposite pattern (e.g., Miethe & Moore, 1986;.…”
Section: Extralegal Disparities In Sentencing: An Overviewsupporting
confidence: 69%
See 1 more Smart Citation
“…Similar results also have been observed in studies of non-traditional sentencing outcomes, including the assignment of the habitual offender designation (Caravelis et al, 2011;Crawford et al, 1998) and the withholding of felony adjudication (Bontrager et al, 2005). However, within the broad categories of violent and drug offenses, there is mixed evidence that racial/ethnic disparities are amplified in less serious cases (Kautt & Spohn, 2002;Lehmann, 2020;Spohn & Cederblom, 1991;Steen et al, 2005). The interactive effects of minority status and criminal history are likewise somewhat inconsistent; while some work has revealed aggravated disparities among offenders with little or no prior record (e.g., Franklin & Henry, 2020;Hester & Hartman, 2017;Spohn & Cederblom, 1991), others have found the opposite pattern (e.g., Miethe & Moore, 1986;.…”
Section: Extralegal Disparities In Sentencing: An Overviewsupporting
confidence: 69%
“…Along these lines, Spohn and Cederblom's (1991) "liberation hypothesis" anticipates that judicial discretion will be largely constrained in more serious cases given the presence of higher evidentiary quality and the predominance of legally relevant concerns. In contrast, as the seriousness of the case at hand decreases, information about the offender becomes more limited, greater ambiguity surrounds the appropriate punishment, and court actors have more discretion over the sentencing process (Hauser & Peck, 2017;Hester & Hartman, 2017;Lehmann, 2020). This perspective is commonly used to interpret the findings regarding the presence of stronger race/ ethnicity effects in the sentencing of less serious offenses and offenders with less extensive criminal histories.…”
Section: Understanding Sentencing Disparitiesmentioning
confidence: 99%
“…However, not all recent work supports typescript theory. For example, Lehmann’s (2020) recent analysis of sentencing of violent offenders in Florida found that White offenders were sentenced more harshly for crimes not associated with racial or ethnic minority status (sexual offenses and abuse of children). Thus, while this line of reasoning runs counter to many of the theoretical perspectives on the relationship between race/ethnicity and sentencing outcomes (Sampson & Lauritsen, 1997; Steffensmeier et al, 1998), this perspective posits that because charges of selling and distributing drugs are seen as “atypical” for White individuals, then White drug offenders should receive harsher dispositional outcomes relative to Black or Hispanic drug offenders (Leiber et al, 2017).…”
Section: Race Ethnicity and Punishment Disparitiesmentioning
confidence: 99%